2017
DOI: 10.1159/000478100
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of S100A14 Expression in Lung Adenocarcinoma

Abstract: Background: Several studies have reported that S100A14 plays important roles during different steps of the tumorigenic process and tumor progression of several types of cancer. The aim of the present study was to investigate the clinicopathological and prognostic significance and functional roles of S100A14 in lung adenocarcinoma. Patients and Methods: S100A14 expression was immunohistochemically studied in 166 consecutive resected lung adenocarcinomas, and its correlation with clinicopathological parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…and Hu et al . found that S100A14 overexpression is associated with tumor metastasis and S100A14 knockdown by RNA interference leads to dramatically reduced migration and invasion of these cells . However, Zhu et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…and Hu et al . found that S100A14 overexpression is associated with tumor metastasis and S100A14 knockdown by RNA interference leads to dramatically reduced migration and invasion of these cells . However, Zhu et al .…”
Section: Discussionmentioning
confidence: 97%
“…10 Katono et al and Hu et al found that S100A14 overexpression is associated with tumor metastasis and S100A14 knockdown by RNA interference leads to dramatically reduced migration and invasion of these cells. 11,12 However, Zhu et al found that S100A14 expression is negatively correlated to cell migration and invasion in gastric cancer. S100A14 blocks store-operated Ca2+ influx by inhibiting Orai1 and STIM1 expression, leading to FAK activation, MMP downregulation, and focal adhesion assembly.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, there are several studies trying to identify how S100A14 is implicated in tumorigenesis by conducting experiments on cancer cell lines. However, it seems that S100A14 affects tumorigenic processes in a different way in different types of malignancies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). In particular, S100A14 enhances proliferation and cell growth in breast (13), cervical (17), ovarian (18) and hepatocellular cancer (19), whereas it inhibits them in oral (23), esophageal (24) and urothelial cancer (27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S100A14 facilitates cell migration in breast (14-16), cervical (17), ovarian (18), hepatocellular (19) and lung cancer (20,21), while it restrains it in gastric cancer (26). Similarly, under the influence of S100A14, motility is increased in breast cancer (15,16), but decreased in urothelial cancer (27), and invasiveness is increased in breast 16, cervical (17), ovarian (18), hepatocellular (19) and lung cancer (20,21), but decreased in oral (22) and gastric cancer (26). Finally, S100A14 seems to promote cell differentiation in esophageal (24) and gastric cancer (26), while it mediates epithelial-to-mesenchymal transition in cervical cancer (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation